The accuracy of virtual setup in simulating treatment outcomes in orthodontic practice: a systematic review - Benja Sereewisai; Rochaya Chintavalakorn; Peerapong Santiwong; Theerasak Nakornnoi; Siew Peng Neoh; Kawin Sipiyaruk (Nature Publishing Group, 2023)
Abstract Objectives To evaluate the accuracy of virtual orthodontic setup in simulating treatment outcomes and to determine whether virtual setup should be used in orthodontic practice and education. Materials and Methods A systematic search was performed in five electronic databases: PubMed, Scopus, Embase, ProQuest Dissertations & Theses Global, and Google Scholar from January 2000 to November 2022 to identify all potentially relevant evidence. The reference lists of identified articles were also screened for relevant literature. The last search was conducted on 30 November 2022. Results This systematic review included twenty-one articles, where all of them were assessed as moderate risk of bias. The extracted data were categorized into three groups, which were: (1) Virtual setup and manual setup; (2) Virtual setup and actual outcomes in clear aligner treatment; (3) Virtual setup and actual outcomes in fixed appliance treatment. There appeared to be statistically significant differences between virtual setups and actual treatment outcomes, however the discrepancies were clinically acceptable. Conclusion This systematic review supports the use of orthodontic virtual setups, and therefore they should be implemented in orthodontic practice and education with clinically acceptable accuracy. However, high-quality research should be required to confirm the accuracy of virtual setups in simulating treatment outcomes.